WhatsApp and atopic dermatitis: a clinical trial - Thaís Braga Cerqueira; Renata Robl Imoto; Mariana Muzzolon; Vânia Oliveira de Carvalho (Jornal de Pediatria)
Objective: To evaluate the effect of text messages with information about atopic dermatitis (AD) on the quality of life (QoL) of children and their caregivers and on the severity of the disease. Methods: Researcher-blinded randomized controlled clinical trial. The experimental group (EG) received messages about AD and the control group (CG) about general health. A total of 56 children under 15 years of age and their caregivers, allocated to the CG and EG, were assessed on admission, after one month, and after four months. Improvement in QoL was measured by the Children's Dermatology Life Quality Index (CDLQI), the Infants’ Dermatitis Quality of Life Index (IDQOL), and the Dermatitis Family Impact Questionnaire (DFIQ), and improvement in the severity of AD by the Scoring of Atopic Dermatitis (SCORAD) and the Eczema Area and Severity Index (EASI). Results: Median age was of nine years, 33 (58.9 %) were girls. The CG and EG had similar results, except for the higher frequency of mild AD in the CG and moderate/severe AD in the EG—these severity categories were kept grouped together. Regarding mild and moderate/severe AD in the EG, the SCORAD score decreased (p = 0.03 and p < 0.001). The EASI in both groups showed a significant reduction (mild AD: CG: p = 0.01, EG: p = 0.04; moderate/severe AD: CG: p = 0.05, EG: p = 0.02). The QoL of children and caregivers improved only in the EG (p = 0.01). Intergroup analysis showed no differences. Conclusion: The improvement in the severity of AD in both groups suggests the positive effects of educational interventions in general, not only those specific to the disease.